Low Growth Sensitivity and Fast Replenishment of Non-structural Carbohydrates in a Long-Lived Endangered Conifer After Drought - Urrutia-Jalabert, Rocío; Lara, Antonio; Barichivich, Jonathan; Vergara, Nicolás; Rodriguez, Carmen Gloria; Piper, Frida I. (Frontiers in Plant Science, 2020)
There is an ongoing debate on whether a drought induced carbohydrate limitation (source limitation) or a direct effect of water shortage (sink limitation) limit growth under drought. In this study, we investigated the effects of the two driest summers recorded in southern Chile in the last seven decades, on the growth and non-structural carbohydrates (NSC) concentrations of the slow-growing conifer Fitzroya cupressoides. Specifically, we studied the seasonal variation of NSC in saplings and adults one and two years after the occurrence of a two-years-drought at two sites of contrasting precipitation and productivity (mesic-productive versus rainy-less productive). We also evaluated radial growth before, during and after the drought, and predicted that drought could have reduced growth. If drought caused C source limitation, we expected that NSCs will be lower during the first than the second year after drought. Conversely, similar NSC concentrations between years or higher NSC concentrations in the first year would be supportive of sink limitation. Also, due to the lower biomass of saplings compared with adults, we expected that saplings should experience stronger seasonal NSC remobilization than adults. We confirmed this last expectation. Moreover, we found no significant growth reduction during drought in the rainy site and a slightly significant growth reduction at the mesic site for both saplings and adults. Across organs and in both sites and age classes, NSC, starch, and sugar concentrations were generally higher in the first than in the second year following drought, while NSC seasonal remobilization was generally lower. Higher NSC concentrations along with lower seasonal NSC remobilization during the first post-drought year are supportive of sink limitation. However, as these results were found at both sites while growth decreased slightly and just at the mesic site, limited growth only is unlikely to have caused NSC accumulation. Rather, these results suggest that the post-drought dynamics of carbohydrate storage are partly decoupled from the growth dynamics, and that the rebuild of C reserves after drought may be a priority in this species.